Remote Control Techniques to the Digital Storage Oscilloscope by GPIB and VISA - Faquan Zhang; Guofu Wang; Jincai Ye; Qingning Zeng (Institute of Advanced Engineering and Science, 2013)
Some techniques of controlling remotely the digital storage oscilloscope were proposed including VISA, VXIplug&play drivers, TVC and IVI-COM drivers. By means of GPIB and VISA, several application development environments could be used to develop remote control techniques to the digital storage oscilloscope. The programming language of Visual C++ was used to develop software. With the help of VISA and the dynamic link library, remote control to the digital storage oscilloscope through network was completed. All operations to the digital storage oscilloscope including parameters setup, data acquisition, waveform acquisition and storage, data processing were implemented in a remote place. The results show that the techniques of remote control are convenient and efficient and fit for experiments of scientific research and practical projects. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2339